Dimensões das furcas de primeiros pré-molares superiores e sua relação com curetas periodontais - Dantas, Carolina Delmondes Freitas; Cavassim, Rodrigo [UNESP]; Pinto, Shelon Cristina Souza [UNESP]; Cirelli, Joni Augusto [UNESP]; Sampaio, José Eduardo Cezar [UNESP]; Bolini, Paulo Domingos André [UNESP] (My University, 2010)
The aim of this in vitro study was to comparatively evaluate the mesio and distal furcation entrance measurements of first maxillary premolar. The measurements were compared with different curette blades. A caliper was used by an examinator to acquire the measurements of root trunk (TR); 1 mm (D1) and 2 mm (D2) both below the furcation entrance. For this study Gracey, Mini Gracey, Padua Lima (PL) and Goldman Fox 4 curettes (Millenium) were selected. Measurements of DT - total distance of the active blade length, DI - width of the active blade, DM - width of the medium part of the active blade were obtained for the curettes. The measurements were obtained in both the coronary face and in the lateral face. The data TR, D1 and D2 presented normal distribution and were statistically analyzed by paired t-test. Statistically significant differences were found in the mesial root trunk region (TR) of both premolars. The mean of the measurements was greater than the distal. Mean and standard deviation were obtained, and both Gracey and Mini Gracey showed mean measurements compatible with the closer furcation entrance (D1 - 1 mm). Goldman Fox 4 showed adaptation only in the mesial face, and Padua Lima showed no access to any of the faces. Thereby it is concluded that the access of the furcation is narrow (D1). The mesial face of the root trunk (TR) showed mean measurement greater than distal face. Gracey and Mini Gracey curettes demonstrated to be compatible for both faces, mesial and distal of the first maxillary premolars studied.

O objetivo deste estudo foi avaliar comparativamente as dimensões das entradas das furcas mesial e distal de primeiros pré-molares superiores extraídos e compará-las com as dimensões das lâminas de diversos tipos de curetas. Foram mensuradas, com paquímetro digital (Digital-Cal Plus, Brown & Sharpe, Co. Ltda.), as distâncias de tronco radicular (TR) a 1 mm (D1) e 2 mm (D2) abaixo da entrada da furca. As curetas selecionadas foram: Gracey, Mini Gracey, Pádua Lima (PL) e Goldman Fox 4 (todas da marca Millenium); obtendo-se as seguintes medidas tanto pela face coronária quanto lateral: DT - distância total do comprimento da lâmina ativa; DI - largura da extremidade da ponta ativa; DM - largura da porção média da ponta ativa. Os dados TR, D1 e D2 apresentaram distribuições normais, sendo analisados pelo teste paramétrico t pareado. Diferença estatística significante foi encontrada na região do tronco radicular (TR) mesial de ambos os primeiros pré-molares, mostrando média das mensurações maior que a distal. Foram obtidas médias e desvio-padrão das curetas, sendo que tanto Gracey quanto Mini Gracey apresentaram mensurações médias compatíveis com a entrada da furca mais estreita (D1 - 1 mm). A Goldman Fox 4 apresentou adaptação apenas nas faces mesiais, e a Pádua Lima não mostrou acesso a nenhuma das faces. Conclui-se que a abertura da furca é estreita (D1); o lado mesial do tronco radicular (TR) tem mensurações médias maiores que o lado distal; as curetas Gracey e Mini Gracey apresentaram-se compatíveis para ambas as faces, mesial e distal dos primeiros pré-molares superiores estudados.
Furcations entrance dimensions of first maxilary premolars and its relation with periodontal curettes
Keywords: Premolar; Dental instruments; Dental scaling; Furcation defects; Dentes pré-molares; Instrumentos odontológicos; Raspagem dentária; Defeitos da furca